A method of sidelobe effect suppression for multibeam water column images based on an adaptive soft threshold. (May 2019) - Liu, Hongxia; Yang, Fanlin; Zheng, Shuangqiang; Li, Qianqian; Li, Donghui; Zhu, Hongchun
Graphical abstract: Highlights: The sidelobe noise is eliminated in a specific direction. The algorithm effectively improves the utilization of data. The target details are effectively preserved by adjusting the soft threshold. Abstract: Recording abundant back scatter information in the water, multibeam sonar water column imaging (WCI) has become one of the most effective means for the acoustic remote sensing investigation of water targets and has been applied and developed rapidly for sounding, fishery, oceanography and archaeology applications as well as in other industries in recent years. Due to the signal interference caused by the sidelobes, there is a great deal of noise in non-target areas of WCI, which reduces the accuracy and efficiency of interpretation of WCI and hinders the automatic detection and recognition of underwater objects. In this paper, an adaptive soft threshold denoising algorithm for WCI is proposed. The WCI data are divided into background areas and target-noise mixing areas by analysing the mathematical features of all angle sequences; thus, the target, noise, and sidelobe artefacts are separated using adjustable threshold parameters and by suppressing noise and sidelobe artefacts to obtain a clearer image. Lastly, the measured data are used for verification. The results indicate that the algorithm has a certain reference value for sidelobe suppression of multibeam WCI.